Exploiting the STAT3 Nexus in Cancer-Associated Fibroblasts to Improve Cancer Therapy - Allam, Amr; Yakou, Marina; Pang, Lokman; Ernst, Matthias; Huynh, Jennifer (Frontiers in Immunology, 2021)
The tumor microenvironment (TME) is composed of a heterogenous population of cells that exist alongside the extracellular matrix and soluble components. These components can shape an environment that is conducive to tumor growth and metastatic spread. It is well-established that stromal cancer-associated fibroblasts (CAFs) in the TME play a pivotal role in creating and maintaining a growth-permissive environment for tumor cells. A growing body of work has uncovered that tumor cells recruit and educate CAFs to remodel the TME, however, the mechanisms by which this occurs remain incompletely understood. Recent studies suggest that the signal transducer and activator of transcription 3 (STAT3) is a key transcription factor that regulates the function of CAFs, and their crosstalk with tumor and immune cells within the TME. CAF-intrinsic STAT3 activity within the TME correlates with tumor progression, immune suppression and eventually the establishment of metastases. In this review, we will focus on the roles of STAT3 in regulating CAF function and their crosstalk with other cells constituting the TME and discuss the utility of targeting STAT3 within the TME for therapeutic benefit.